Investigation of the Presence of Chicken Parvovirus in Turkish Backyard Poultry Flocks: A Comparative Analysis of PCR Primer Sets - Turan, T; Kalin, R; Isidan, H; Atasoy, MO (Journal of the Hellenic Veterinary Medical Society, 2024)
Enteric syndromes such as runting-stunting syndrome or malabsorption syndrome cause significant economic loss in industrial-scale poultry production. These syndromes are commonly perceived to possess a multifactorial aetiology; nevertheless, the extent of parvoviral involvement remains largely obscure. In addition, A potential reservoir of parvoviruses might be the backyard flocks, where the less precautions are undertaken. In this study, we aimed to investigate the potential participation of chicken parvovirus in enteric diseases of the farmyard layers belonging to semi-professional producers by comparing various PCR primer sets. 404 faecal samples from eight provinces were collected. The ChPV was studied from all samples by five PCR methods including nested and conventional PCR assays using different primer set combinations. Some samples were further sequenced, and the outputs were analysed in silico. The significantly varied positivity percentages depending on PCR methods (7.9 – 44.6%) were observed in faecal samples of backyard flocks. Phylogenetic analysis results further revealed the varied level of nucleotide identity (94.51% to 99.10) and the obtained Turkish strains were mainly distributed into two different clusters. The nested PCR approach developed in this study might be an alternative to other conventional PCR primers owing to its increased sensitivity. In addition, data represented the first identification of ChPV strains in Turkish poultry. Overall, the results pinpointed the increasing health risk in backyard poultry production stemming from ChPV infections and revealed the requirement for biosecurity precautions to prevent disease transmission.